Observation of photon recoil effects in single-beam absorption spectroscopy with an ultracold strontium gas - Hu, Fachao; Tan, Canzhu; Jiang, Yuhai; Weidemüller, Matthias; Zhu, Bing (Chinese physics, 2021)
We report on observing photon recoil effects in the absorption of a single monochromatic light at 689 nm through an ultracold 88Sr gas, where the recoil frequency is comparable to natural linewidth of the narrow-line transition 5s2 1S0 - 5s5p 3P1 in strontium. In the regime of high-saturation, the absorption profile becomes asymmetric due to the photon-recoil shift, which is of the same order as the natural linewidth. The lineshape is described by an extension of the optical Bloch equations including the momentum transfers to atoms during emission and absorption of photons. Our work reveals the photon recoil effects in a simplest single-beam absorption setting, which is of significant relevance to other applications such as saturation spectroscopy, Ramsey interferometry, and absorption imaging.
Gesehen am 21.10.2021